Short-term Functional Outcomes and Complications of Custom Patellofemoral Arthroplasty - Joshua T. Rogers, MD; Jack A. Nolte, MD; Brayden Strine, MD; Rosey Zackula, MA; Jake Bianco, MD; Tarun Bhargava, MD (Arthroplasty Today, 2024)
Background: Patellofemoral arthroplasty (PFA) is a treatment option for isolated patellofemoral arthritis. Custom PFA is an innovative procedure utilizing patient-specific instrumentation. The purpose of this study is to evaluate short-term functional outcomes and complications of the custom PFA in treatment of isolated patellofemoral arthritis. Methods: A retrospective study was conducted to analyze patients who received a PFA operation from a single surgeon. Inclusion criteria were surgical patients from 2012 to 2018 who underwent PFA using a custom prosthesis implant. Knee injury and Osteoarthritis Outcome Score for Joint Replacement (KOOS, JR) and Lower Extremity Functional Scale (LEFS) were collected before and after surgery. Results: A total of 79 patients (94 knees) participated in the study; 55 (69.6%) were women. The median age was 57 at the time of index arthroplasty; 15 patients (30 knees) were bilateral. Follow-up rate was 94%. Median follow-up duration was 3.6 years (2-8.9). Overall prefunctional and postfunctional scores differed significantly for both KOOS, JR and LEFS. Postoperative scores increased for KOOS, JR by 27.5 points, and for LEFS, they increased 26.0 points; P < .001 for both. Complications included 6 reoperations (6.7%) related to PFA: 4 conversions (4.4%) to total knee arthroplasty at a median of 2.5 (1.5-3) years after the index procedure, one vastus medialis oblique advancement (1.1%) secondary to patellar maltracking, and one manipulation under anesthesia (1.1%). Conclusions: Custom PFA in patients with isolated patellofemoral arthritis showed good short-term functional outcomes and low revision rates with very few complications.